2015
DOI: 10.1097/icl.0000000000000129
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Collagen Cross-linking on Psychological Distress and Vision and Health-Related Quality of Life in Patients With Keratoconus

Abstract: Our results suggested lower trait anxiety and better vision-related and health-related QoL in KC patients 1 year after successful CXL treatment. Better QoL in these patients seems to be related not only with the visual and refractive results but also improvement observed in trait anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 31 publications
3
24
0
2
Order By: Relevance
“…Although the hypothesis that KC is accompanied by depression has been rejected by Woodward et al [ 32 ], this association appeared to demonstrate a gender bias [ 31 ]. Cingu et al reported significant improvement of anxiety after cross-linking (CXL) in KC patients; however, this intervention did not appear to influence the depressive status of KC patients [ 41 ]. To the best of our knowledge, our study is the first to report a significant association between depression and KC, regardless of the participants' age and gender, by assessing two different questionnaires simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Although the hypothesis that KC is accompanied by depression has been rejected by Woodward et al [ 32 ], this association appeared to demonstrate a gender bias [ 31 ]. Cingu et al reported significant improvement of anxiety after cross-linking (CXL) in KC patients; however, this intervention did not appear to influence the depressive status of KC patients [ 41 ]. To the best of our knowledge, our study is the first to report a significant association between depression and KC, regardless of the participants' age and gender, by assessing two different questionnaires simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 13 , 23 Detailed grading for anxiety/depression such as “State-Trait Anxiety Inventory” could not be performed in this study. 24 , 25 In addition, it was not clear whether anxiety/depression is a temporary condition to symptom or a general tendency in subjects with undiagnosed glaucoma. It could be one of limitations that quantitative or qualitative evaluation for depression was not possible in this study, even though a brief screening questionnaire needed a shorter time.…”
Section: Discussionmentioning
confidence: 99%
“…The group which was not using contact lenses was ones which have not been motivated to use lenses .Many of them have not been told much about them because the ophthalmological clinics do not have facilities to fit them. Fitting contact lens requires skills and a range of fitting sets .These facilities are mostly available at the tertiary centers .Patients in small towns and poor awareness about the contact lens options by ophthalmologists lead to letting the patient continue with the spectacles .Funicular keratoconus is the worst, where the patient is made to continue with one eye vision [19][20][21][22]. Many times the patients have been fitted with lenses and the bad experience of ill fitting lenses have led to the drop out.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional ties:Is a type of emotional bond that acts like an elastic band as it stretches and relaxes due to our emotional thoughts and behaviours toward one another [22] .…”
Section: Loss Of Behavioural/emotional Controlmentioning
confidence: 99%